The economics of home support services in Ireland: exploring complex issues of healthcare sustainability and aging populations - Morrow, Elizabeth; Lynch, Mary (Frontiers in Public Health, 2025)
BackgroundHome support is a critical yet under-recognized component of public health and aging policy, with economic perspectives often overlooked in workforce and system planning. This paper explores the economics of home support services in Ireland, against a backdrop of increasing demand for home care driven by aging populations and workforce supply challenges.AimsTo provide a comprehensive overview of the economic challenges faced by the home support sector in Ireland, particularly in relation to workforce sustainability, population health, and quality service delivery. To explore international best practices and case studies that can further inform the development of home support models.MethodsUtilizing both qualitative and quantitative population, labor force, and health service data, the analysis of the Irish context investigates three critical areas: (1) the rising demand and funding of home support, (2) cost comparisons with institutional care, and (3) the economic implications of workforce expansion. Systematic literature review of the international evidence used a structured search of electronic databases (Web of Science, MEDLINE, CINHAL) using key terms (“home support,” “workforce development,” and “economic or cost”) to identify a range of recent (published 2015–2025) and relevant case studies to inform policy development.ResultsFindings indicate that Ireland’s market-driven approach, heavily reliant on approved private providers, exacerbates issues like low wages, job insecurity, and high staff turnover, which negatively impact service quality. Implications for healthcare workforce policy include improving wages and working conditions, establishing career pathways and professional development, and increased government investment. Recommendations for policy include making strategic investments in workforce stability and better integration of home support with informal care systems to enhance service delivery.ConclusionPolicymakers can inform themselves about the economic considerations for developing a robust home support system in the context of aging populations. Further research is needed into the assumptions and validity of financial decisions to ensure services are sustainable.